(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
HumanÂ motionÂ analysisÂ concernsÂ the detection,Â trackingÂ andÂ recognitionÂ ofÂ peopleÂ behaviors,Â from imageÂ sequencesÂ involvingÂ humans. AÂ referenceÂ frameÂ isÂ initiallyÂ usedÂ andÂ consideredÂ asÂ backgroundÂ information. While a new object enters into the frame, the foreground information and background information are identified using the reference frame as background model.In this paper, an efficient algorithm is proposed for objects detection in real time video sequences. The method aims at tracking an object like (human) in motion using background subtraction technique. The tracked objects are subject to different pre and post image processing in order to extract the most important features (frame preprocessing is used for shadow removal using morphological operations). They can be used later for recognition in different security system such as (human detection for surveillance). Experimental results show that the proposed method is very efficient in terms of reliability and accuracy of detection.